IDENTIFIKASI PERILAKU BERPACARAN REMAJA BERDASARKAN TEORI PRECEDE-PROCEEDE - Adelina Hazhiyah Saraya; Ari Pristiana Dewi; Rismadefi " Woferst (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
Abstract This study aims to identify adolescent dating behavior based on precede-proceede theory. Dating is relationship between two people in love such as meet in one place that has been stated/ planed with as related in relationship. Adolescent are individuals who were in period of transition from childhood in to adulthood, beginning around 10 years old to 13 years old and ended between the ages of 18 years old to 22 years old,and is characterized with very rapid development from physical, psychological, and social aspects. Precede-proceede theory is one of theory and model in nurse comunity to show the sympton/phenomenom which is affect the individual behavior. This research used quantitative approach with descriptive method with sampling  technique using purposive sampling. The results of this research to show the total of respondents who are obey the religion norm around 79 respondents (87.8%) coeval infect around 74 respondents (91.1%), parents roles around 82 (91.1%)  total of who has dating more than once is 58 students (64.4%), and total of students was participated in organizatin around 62 respondents (68.8%). The recomendation in this research is a practical action that can be adapted by parents or teacher to provide or to teach the value or norm in dating Keywords: dating, adolescent and  precede-proceede theory